Bold! Daring! Shocking! True! : A History of Exploitation Films, 1919-1959 - Schaefer, Eric, 1959- (Book collections on Project MUSE., 1999)
'Trash films' purveyed the forbidden thrills of explicit sexual behaviour, drug use and vice that the mainstream Hollywood film industry could not show. Setting these exploitation films in their historical context, and organising them according to the social problems they addressed, Schaefer shows how the films evolved and shaped public policy and attitudes in America over 40 years.